Loyalty Programs and Customer Retention in the Hospitality Sector: A Study at Rumah Jawa Syariah Guest House - Hartanto, Ramadhan Bagus; Adilla, Fitroh; Setiawan, Zunan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This qualitative study investigates the role of loyalty programs in enhancing customer retention within the hospitality sector, focusing on Rumah Jawa Syariah Guest House as a case study. The research aims to uncover how loyalty initiatives influence guests’ decisions to return and maintain long-term engagement. Using in-depth interviews with guests and management, complemented by direct observations and document analysis, the study explores the experiences, perceptions, and motivations that shape customer loyalty. Findings indicate that loyalty programs significantly contribute to emotional attachment and overall satisfaction, which in turn foster higher retention rates. Key elements that enhance program effectiveness include personalized rewards, clear and consistent communication, attentive service quality, and the sense of being valued by the guest house. The study also reveals that guests respond positively when loyalty programs emphasize meaningful engagement rather than solely material incentives, highlighting the importance of relationship-centered strategies. These insights provide practical guidance for hospitality managers seeking to design loyalty initiatives that cultivate authentic connections with customers while sustaining competitive advantage. On a theoretical level, the research emphasizes the relevance of a human-centered approach to loyalty management, demonstrating that qualitative methods are essential for capturing the nuanced dynamics of consumer behavior in the context of Sharia-compliant hospitality. The study contributes to both academic understanding and managerial practice by bridging customer experience, loyalty program design, and retention strategies in small-scale hospitality settings.